Performance analysis of CMOS based analog circuit design with PVR variation - Prajapati, Pankaj P.; Kshatriya, Anilkumar J.; Bharvad, Sureshbhai L.; Upadhyay, Abhay B. (Institute of Advanced Engineering and Science, 2023)
Process, supply voltage, and temperature (PVT) are three important factors which contribute to performance variation of the complementary metal–oxide–semiconductor (CMOS) based analog circuits. In this paper, CMOS based analog circuit design with the PVT variation effects are explored. The effects of the PVT variation on the performance of CMOS based analog circuits are introduced. The optimization of CMOS based analog circuits such as differential amplifier (DA) and two-stage operational amplifier (op amp) circuits with PVT variations with different algorithms such as cockoo search (CS), particle swam optimization (PSO), hybrid CSPSO, and differential evaluation (DE) algorithms is presented. Each algorithm is implemented using the C programming language, interfaced with Ngspice circuit simulator, and tested on the Intel®core™ i5, 2.40 GHz processor with 8 GB internal RAM using the Ubuntu operating system (OS). The result shows PVT variation affects the performance of CMOS circuit.